2017
DOI: 10.1111/jav.01393
|View full text |Cite
|
Sign up to set email alerts
|

The long shadow of senescence: age impacts survival and territory defense in loons

Abstract: Senescence, increased mortality that occurs among animals of advanced age, impacts behavior and ecology in many avian species. We investigated actuarial, reproductive, and behavioral senescence using capture, marking, and resighting data from a 26‐year study of common loons Gavia immer. Territorial residents of both sexes exhibited high annual survival (0.94) until their mid 20s, at which point survival fell to 0.76 and 0.77 in males and females, respectively. Sexual symmetry in actuarial senescence is somewha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…The ageing of these traits was highly asynchronous, with variable rates and durations of both early-adulthood improvements and late-life declines, with some traits not showing any period of maturation in early adulthood, and others not showing senescence. Our results add to the growing body of empirical evidence that traits do not senescence synchronously within an individual (Nussey et al 2009;Froy et al 2013;Hayward et al 2013Hayward et al , 2015Zhang et al 2015;Piper et al 2017;Tompkins and Anderson 2018). Below we discuss how the patterns of ageing in fairy-wrens fit with theory and empirical research on ageing, and consider how the distinctive ecological and evolutionary forces faced by this species may be driving these patterns.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The ageing of these traits was highly asynchronous, with variable rates and durations of both early-adulthood improvements and late-life declines, with some traits not showing any period of maturation in early adulthood, and others not showing senescence. Our results add to the growing body of empirical evidence that traits do not senescence synchronously within an individual (Nussey et al 2009;Froy et al 2013;Hayward et al 2013Hayward et al , 2015Zhang et al 2015;Piper et al 2017;Tompkins and Anderson 2018). Below we discuss how the patterns of ageing in fairy-wrens fit with theory and empirical research on ageing, and consider how the distinctive ecological and evolutionary forces faced by this species may be driving these patterns.…”
Section: Discussionsupporting
confidence: 74%
“…In recent years, it has become possible to characterize this "generalized deterioration" by measuring the ageing of multiple fitness-related traits in wild animal populations. However, the empirical evidence to date suggests that, rather than senescing in unison, either the onset of senescence, or the rates of senescent declines often vary between different phenotypic traits (for example, Bouwhuis et al 2012;Massot et al 2011;Preston et al 2011;Froy et al 2013;Hayward et al 2013;Berger et al 2015a;Zhang et al 2015;Hammers et al 2015;Kervinen et al 2015;Piper et al 2017). In a recent review, Bouwhuis and Vedder (2017) show that, amongst longitudinal studies of ageing in wild bird populations, performance declines are most often reported for physiological traits (89% of which show a decline), and less so for traits involved in reproductive performance (67%) or traits associated with sexual selection (50%).…”
Section: Introductionmentioning
confidence: 99%
“…The ageing of these traits was highly asynchronous, with variable rates and durations of both early-adulthood improvements and late-life declines, with some traits not showing any period of maturation in early adulthood, and others not showing senescence. Our results add to the growing body of empirical evidence that traits do not senescence synchronously within an individual (Nussey et al 2009;Froy et al 2013;Hayward et al 2013Hayward et al , 2015Zhang et al 2015;Piper et al 2017;Tompkins and Anderson 2018). Below we discuss how the patterns of ageing in fairy-wrens fit with theory and empirical research on ageing, and consider how the distinctive ecological and evolutionary forces faced by this species may be driving these patterns.…”
Section: Discussionsupporting
confidence: 74%
“…The lack of an impact of male age on abandonment provides an interesting contrast to females and sheds more light on the sexual difference in breeding success with age among loons. Both sexes senesce, as annual survival rate falls steeply when loons reach their mid-20s, but fledgling production increases with age in males, while showing no clear change in females (Piper et al 2017). The fact that old males resist nest abandonment better than old females is consistent with the conclusion that males, but not females, might make a terminal investment in incubation that accounts, at least in part, for their greater fledgling production (Piper et al 2017).…”
Section: Effect Of Female Age On Nest Abandonmentsupporting
confidence: 72%
“…Recent work has shown that loons of both sexes senesce once they reach their mid-20s (Piper et al 2017). Since old birds of many species show declines in reproductive performance with age (e.g., Reed et al 2008, Sergio et al 2011, Pardo et al 2013, the strong tendency for pairs containing old females to abandon nests is perhaps not surprising.…”
Section: Effect Of Female Age On Nest Abandonmentmentioning
confidence: 99%